Deficiencies and Toxicities of Some Nutrient Elements in Acid Sulfate Soils of Thailand - Tasnee Attanandana (Agriculture and Natural Resources, 1993)
This paper reviews the works on nitrogen, and phosphorus deficiencies and kinetics of Fe and Al in acid sulfate soils of Thailand. The research revealed that rice plants response to nitrogen fertilizer due to the low N mineralization rate especially soils with high acidity. Addition of organic waste materials resulted in lower mineralizable N in acid sulfate soils compared to non acid sulfate soils. Response to phosphorus fertilizer was due to low total P content and high P - fixation capacity. P - sorption studies of the soils confirmed this results. In the very acidic acid sulfate soils, no grain yield was obtained without phosphate application. Iron and aluminum are the two important toxic elements in acid sulfate soils. However, the soluble content was less in acid sulfate soils in Thailand compared to acid sulfate soils in Vietnam. Thus, no toxicity of these two elements has been reported. The toxicity symptoms of the two elements could be found when oxidized potential acid sulfate soil was leached and limed.